Pure Decompression versus Decompression with Fusion in Degenerative Lumbar Spondylolisthesis: A Meta-Analysis of Long-Term Outcomes - Andika Prasetyo Arifin; M. Yogi Alamsyah; Arimurti Pratianto; Rheza Fabianto Sebastian (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Degenerative lumbar spondylolisthesis is a common spinal problem seen in everyday practice, especially in older adults, and it often presents with ongoing low back pain, neurogenic claudication, and radicular symptoms. Although decompression surgery is generally considered effective for relieving neural compression, whether fusion should be added at the same time is still controversial, particularly when long-term results and resource use are taken into account. This meta-analysis followed PRISMA guidelines. We systematically searched PubMed, the Cochrane Library, and Google Scholar for randomized controlled trials involving adults with degenerative lumbar spondylolisthesis. The main outcomes were functional disability measured by the Oswestry Disability Index (ODI), along with separate assessments of low back pain and leg pain. Data were pooled in Review Manager 5.4 using fixed- or random-effects models as appropriate, and results were reported with 95% confidence intervals. Across the three included trials, the two surgical strategies performed similarly overall. There were no meaningful differences in ODI scores or in reported back and leg pain. Decompression alone was linked to a slightly higher reoperation rate, but the difference was not statistically significant. In contrast, adding fusion led to longer operative times and longer hospital stays, without providing a clear clinical benefit. Taken together, these findings suggest that decompression without fusion may be a simpler, more resource-efficient choice for carefully selected patients with degenerative lumbar spondylolisthesis who do not have instability or major deformity. That said, the evidence is still limited by the small number of trials and relatively short follow-up. Larger, well-designed studies with longer observation are needed to better determine how durable the outcomes are and what the true reoperation risk is.